From Digital Divides to Digital Dividends: Embracing Basic Services in Zimbabwe's Digitalisation Agenda - Fungai N. Mukora; Teurai Matekenya; Gilbert Mahlangu; Innocent Chirisa; Caroline Hester Sarai Muparutsa (IGI Global, 2023)
Abstract